High-Value Care Culture Among the Future Physician Workforce in Internal Medicine. (September 2019) - Gupta, Reshma; Steers, Neil; Moriates, Christopher; Wali, Soma; Braddock, Clarence H.; Ong, Michael
Abstract : Purpose: Training in high-spending regions correlates with higher spending patterns among practicing physicians. This study aimed to evaluate whether trainees' exposure to a high-value care culture differed based on type of health system in which they trained. Method: In 2016, 517 internal medicine residents at 12 California graduate medical education programs (university, community, and safety-net medical centers) completed a cross-sectional survey assessing perceptions of high-value care culture within their respective training program. The authors used multilevel linear regression to assess the relationship between type of medical center and High-Value Care Culture Survey (HVCCS) scores. The correlation between mean institutional HVCCS and Centers for Medicare and Medicaid Services' Value-Based Purchasing (VBP) scores was calculated using Spearman rank coefficients. Results: Of 517 residents, 306 (59.2%), 83 (16.1%), and 128 (24.8%) trained in university, community, and safety-net programs, respectively. Across all sites, the mean HVCCS score was 51.2 (standard deviation [SD] 11.8) on a 0–100 scale. Residents reported lower mean HVCCS scores if they were from safety-net-based training programs (β = −4.4; 95% confidence interval: −8.2, −0.6) with lower performance in the leadership and health system messaging domain ( P < .001). Mean institutional HVCCS scores among university and community sites positively correlated with institutional VBP scores (Spearman r = 0.71; P < .05). Conclusions: Safety-net trainees reported less exposure to aspects of high-value care culture within their training environments. Tactics to improve the training environment to foster high-value care culture include training, increasing access to data, and improving open communication about value. Abstract : Supplemental Digital Content is available in the text.